Heart failure remote monitoring: novel approaches and management strategies - Proaño Bautista, Cristian Xavier; Tinoco Aguilar, Angie Pauleth; Andrade Valenzuela, Rayza Alexandra; Zamora Pachay, Arellys Jacqueline; Vega Pacheco, Jorge Nicolás (Sapienza: International Journal of Interdisciplinary Studies, 2024)
Background. Globally, heart failure is a leading health problem, with an estimated 64 million cases worldwide, including 6.7 million in the U.S., according to estimates. The U.S. economic burden is expected to see a steep rise by the year 2030. Heart failure is a cause of 8.5% of heart disease-related deaths and a central cardiovascular killer. Emergency hospitalization rates and readmission rates are high. Methods: A systematic methodology was followed to generate authentic and reliable data on remote monitoring in the setting of heart failure patients. The inclusion criteria comprise articles describing remote monitoring interventions published in peer-reviewed journals and carried out in human subjects in English. Critical analysis applies quality assessment tools to assess methodological soundness, possible bias, and relevance to the research objective. Results: This review discusses wearable devices, e.g., Zoll HFMS ReDS, and Audicor, each effectively monitoring cardiac parameters and reducing H.F. hospitalizations. Implantable cardiac monitors such as LUX-Dx and CardioMEMS H.F. RM has potential to give real-time data for timely intervention and tailored therapies. The integration of machine learning algorithms in devices, for example, VitalPatch and the SimpleSense has led to increased use of these devices to make precise and efficient health care predictions, leading to improved patient outcomes. Conclusion: From all the research, remote monitoring devices and strategies are recommendable for patients with various cardiac complications. It can improve heart function, however, R.M. has not been seen to reduce the overall mortality rate among heart patients.